CSR and social entrepreneurship: Combining efforts towards sustainability. Issue 4 (1st October 2020) - Pandey, Satyendra C.; Panda, Swati; Widmier, Scott; Harvey, Eric
ABSTRACT: Distinctions are usually drawn between social entrepreneurship and corporate social responsibility based upon the implications, the impact, and the stimulus required. Limited empirical evidences are there in the existing literature to suggest any connect between social entrepreneurship and corporate social responsibility. This article points out the efforts of development and encouragement of social entrepreneurship as a CSR activity by a large public listed coal mining and refining company. Company makes a significant contribution towards the overall coal production in India. The study field is concentrated around main basin located in Singrauli district of Madhya Pradesh in India. Implications are drawn based upon the success observed in the initiative and future directions and explored.